Optimalisasi distribusi pusat pelayanan perkotaan Usuku Tomia menggunakan Kernel Density Estimation (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2026)
Small island cities face structural challenges in providing service centres due to spatial fragmentation and limited accessibility. This study aims to analyse the spatial structure and optimise the distribution of urban service centres in the Usuku Tomia Urban Area, Wakatobi Regency, using a weighted Kernel Density Estimation (KDE) approach. Data were obtained from field observations of 163 public service facilities spread across 12 villages/subdistricts in Tomia and East Tomia Subdistricts, covering 11 service categories. The analysis was conducted using a descriptive-analytical quantitative method based on a Geographic Information System (GIS) to estimate the spatial intensity of services and establish a hierarchy of service centres. The results of the study show significant spatial inequality and form four service centre hierarchies. The subdistricts of West Tongano and Waha were identified as primary service centres (Order I) with the highest density values (>4.5 units/km²), dominated by high-weight facilities such as education, trade and services, and settlements. Conceptually, these findings expand the application of place centre theory to the context of non-contiguous small island cities. Practically, this study confirms KDE as an evidence-based policy instrument to support more efficient and equitable service centre planning in island regions.
Keywords: Kernel density estimation; Small island city; Spatial structure; Urban service centre; Usuku Tomia